Microwave-Promoted Synthesis of 4-Arylpyrimidines by Pd-Catalysed Suzuki–Miyaura Coupling of 4-Pyrimidyl Tosylates in Water - Rodríguez-Aguilar, José; Ordóñez, Beatriz; Vidal, Matías; Rezende, Marcos Caroli; Domínguez, Moisés (SynOpen, 2017)
The Suzuki–Miyaura coupling reaction of 4-pyrimidyl tosylates was investigated with aryl, heteroaryl and alkyl boronic acids. The reaction provided 4-substituted pyrimidines in good-to-excellent yields after one-hour microwave irradiation in water at 100 °C. The method constitutes a fast option for the synthesis of these heterocyclic systems.
Keywords: Suzuki–Miyaura coupling; pyrimidines; tosylates; microwave-accelerated synthesis; cross-coupling